(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Teaching elementary school students to solve logical problems in mathematics develops critical thinking, problem-solving skills, and analytical reasoning. This thesis explores structured problem-solving models, visual aids, puzzles, real-life applications, and technology-enhanced learning. By fostering logical reasoning through engaging methods, students build confidence and essential skills for academic and real-world challenges.